PERANAN BANTUAN OPERASIONAL PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI TERHADAP AKSES LAYANAN PENDIDIKAN ANAK USIA DINI DI INDONESIA - Lusi Repina Simarmata; Khoirunurrofik (Journal Publicuho, 2024)
There is limited knowledge and information for parents in the process of early childhood growth and development, so the right step for parents is to enrol their children in Early Childhood Education (PAUD) institutions. Government intervention is needed to expand access to PAUD services in Indonesia, one of which is by providing BOP PAUD to PAUD providers. This research uses panel data to analyze the relationship between Operational Assistance for Providing Early Childhood Education (BOP PAUD) and the Gross Participation Rate (APK) for PAUD in Indonesia. Selecting the best panel data model from three types of panel data regression models (Ordinary Least Square ( Pooled Least Square), Fixed Effect Model, and Random Effect Model) can be carried out using the Chow Test, Hausman Test, and Lagrange Multiple Test. Classical assumption tests and model feasibility tests were also carried out using the Feasible Generalized Least Squares (FGLS) estimation technique. PAUD BOP per student was tested with several control variables and the results found that PAUD BOP per student did not have a significant relationship with PAUD APK. Meanwhile, school variables, student-teacher ratio and urban households with their own home status have a significant relationship to PAUD APK.